The taste of a fungus: recognition of Candida by the innate immune system - Gow, Neil (Henry Stewart Talks, 2012)
Immune recognition of fungi, Fungal infections are serious challenges in the clinic, The innate immune system has a pre-eminent role in containing fungal infection, Cell wall mutants of Candida can be used to help discover the nature of the recognition mechanisms, Combining pattern recognition mechanisms can greatly amplify immune response, Candida mannan in recognition, phagocytosis and activation of immune responses, Candida chitin importance in cell wall integrity and immune responses, Candida albicans yeast-hypha morphogenesis: activation and resistance to immune responses